Corporate social responsibility, business and human rights standards in Indonesia - Gayo, Sabela (College of Law, Government and International Studies, Universiti Utara Malaysia, 2012)
Business and human rights issues are very interesting themes to be discussed in the current emerging investment boom, especially in developing countries like Indonesia. Foreign Direct Investment (FDI) has provided a very positive impact in generating economic growth and significantly increasing per capita income of particular countries.But on the other side, it also resulted in several negative impacts for particular situations and conditions, such as environmental, labour, and social issues.The euphoria of foreign direct investments sometimes ignores several human rights principles that must be respected by those investors. This paper would discuss further about business and human rights standards in the Indonesian context, taken from international, national or sub-national cites. Recently, the United Nations Human Rights Council endorsed and adopted John Ruggie’s Guiding Principles for Business and Human Rights which became the United Nations Guiding Principles for Business and Human Rights.It is an international standard on how business practices should behave in the interest of the local people by respecting local wisdom, local values and local cultures which are constantly being highlighted and being concerns of several international and national human rights advocacy organizations. The international standard on business and human rights is quite new in the international law regime but it is highly necessary for stakeholders to deal with several issues related to business and the human rights domain.Corporate Social Responsibility policies and programmes are still being discussed intensively by interest groups on whether they meet the beneficiaries’ satisfactory level as a win-win solution for human rights abuses committed by multinational corporations or are they just a “make up” from multinational corporations to reduce social rejection from local people where they operate.The Content policy analysis and the comparison method with other countries would describe comprehensively the importance of corporate respect for human rights principles and corporate social responsibility practices.